MULTIMEDIA VIRTUAL LABORATORY FOR PHYSICS IN THE DISTANCE LEARNING - H. M. Kravtsov; E.O. Kozlovskiy (Kherson State University, 2014)
It's presented the results of the software module "Virtual Lab" for distance learning system «Kherson Virtual University" (DLS KVU) applied to the problems of physics. Relevance of research due to the absence of existing DLS to support the creation and use of virtual labs in the disciplines of science cycle. The subject of this study is a software module to create and use virtual labs in distance learning system. The purpose of the study is a description of software technology of virtual laboratory in physics for distance learning system. It's described the information technology, which used in design and development, as well as the structure of the virtual laboratory and its place in the DLS KVU. It's described the principal modes of operation of the program module in the system and methods for its use in the educational process. The basic structure of the software module "Virtual Lab" is a multimedia Web editor of virtual labs, which was created using Object-oriented analysis and design technology. Software library of multimedia 3D objects, which was created in the development environment of interactive graphics Unity3D, unifies the process of creating and processing virtual labs. Basic mathematical calculations support the math processor Waterloo Maple. The developed software interface allows teachers to create laboratory and use them in their distance courses. Students, in turn, will be able to conduct research, performing virtual labs.